Technology for Tourism: A Guideline for Best Practices - Zimik, A S Sochipem; Arup Barman (MultiTech Publisher, 2024)
This research employs a comprehensive analysis of technological advancements pertinent to the development of the tourism sector. Drawing upon a synthesis of pertinent literature, the study delineates two primary objectives: firstly, to elucidate the technological attributes relevant to tourism within the framework of Maslow's Hierarchy of Needs, and secondly, to scrutinize the trajectory of technological trends in the tourism industry. Employing a descriptive methodology, the research encapsulates both tangible and intangible facets of these technologies. Identifying existing research lacunae, the study underscores the pivotal role of technology in fostering economic sustainability and growth within the tourism sector. Emphasizing the imperative for innovation via investment in technology, the research advocates for heightened awareness among stakeholders. The study concludes with robust recommendations urging stakeholders to comprehend tourist psychology, devise policies conducive to technological investment, and adeptly manage resources to ensure optimal industry functionality and sustained economic growth.